Does mobile phone technology reduce agricultural price distortions? Evidence from cocoa and coffee industries - Aimable Nsabimana; Franklin Amuakwa-Mensah (Agricultural and Food Economics, 2018)
Agricultural price distortion which is the discrepancy between world market price of agricultural produce and price received by farmers as a result of market interventions by governments, either through subsidies or taxes or even trade protection systems, has received rare attention in the cocoa and coffee sub-sectors. This study examines the contribution of mobile phone technology in reducing price distortions in cocoa and coffee production. In addition, we tested stylized facts such as the development paradox, resource abundance, and group-size effect in agricultural price distortions literature. The findings suggest that access to mobile phones reduces the extent of price distortions. The effect of mobile phone usage on the extent of price distortion, the nominal rate of assistance, and relative price margin is conditional on internet connectivity. Whereas our results support the development paradox and group-size effect hypotheses, the resource abundance hypothesis is not supported. Based on our results, policies that seek to reduce the cost of telecommunication, increase competition in the telecommunication industry, and increase economic growth would go a long way to reduce price distortion in the cocoa and coffee industries.
Keywords: Q1; Q17; E64; 330; Price distortion; Nominal rate of assistance; Relative price margin; Mobile phone; Cocoa; Coffee